Konsep Garap Pakeliran “Wayang Tunggal” Lakon Sudamala Sajian Ki Purbo Asmoro (Relevansi Wayang Sebagai Doa Dalam Fenomena Covid19) - Catur Nugroho (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2021)
This study discusses the wayang performance which is only performed by a dalang alone. The show was referred to as “Wayang Tunggal”. The focus of this research is Wayang Tunggal, Sudamala play, Ki Purbo Asmoro’s presentation. This performance was interesting because it appeared against the backdrop of the Covid-19 pandemic situation. The Sudamala play is a Ruwatan play which means story as a prayer. This study uses an interpretive descriptive concept to discuss the concept of working on pakeliran, including elements of chess, sabet, and pakliran karawitan. The Covid-19 pandemic virus forces almost all elements of life to avoid crowds, while maintaining a safe distance. The single shadow puppet show by Ki Purbo Asmoro is an expression of a very sad reality for both the public in general and the artists in particular. Sudamala’s play is an expression of prayer and hope that the world situation will recover soon, so that everyone can carry out their activities as usual.